ANALISIS SISTEM PEMASARAN CABAI MERAH DI PROVINSI LAMPUNG - Cicelia, Natasha Anandhiepa; Rosanti, Novi; Rahmalia, Dian (Lampung University, 2025)
This study aims to analyze the red chili marketing system in Lampung Province as seen from the market structure, market behavior and market performance. This research method is a survey method conducted in South Lampung Regency and Pesawaran Regency. The determination of respondents was carried out using accidental sampling method with a total of 67 red chili farmers. While the determination of trader respondents is done using snowball sampling technique where the implementation is in a chain that starts with conducting interviews to red chili farmers, then farmers will mention traders who become the next respondents. Research data were obtained from October to December 2023. The data analysis method used is the structure, conduct and performance (SCP) method. The analysis of market structure and market behavior is done descriptively qualitative while market performance is analyzed quantitatively by calculating marketing margin, farmer share, and Profit Margin Ratio. The results of market performance calculations show that the most efficient channel is channel II with consideration of the value of farmers share obtained is higher, the value of marketing margin is lower, the chain of channel II is shorter and the price received by end consumers is smaller than the other two channels.